Kennedy’s disease presented with mastication fatigue combined with positive titin antibody: a case report - Guang Ji; Rui Huang; Xiaomeng Zhou; Cuifang Cao; Qiong Wu; Zhenfei Li; Hui Dong; Xueqin Song; Yaling Liu (BMC Neurology, 2022)
Abstract Background Spinal and bulbar muscular atrophy (SBMA) is an X-linked recessive hereditary neuromuscular disorder caused by the expanded trinucleotide repeat in the androgen receptors gene. The major clinical manifestations of SBMA consist of weakness in the bulbar and limb muscles, fasciculations, tremors, cramps, sensory impairment, and gynecomastia. However, atypical SBMA cases may lead to misdiagnosis. Muscular fatigue and decremental responses to repetitive nerve stimulation (RNS), despite being observed in some SBMA patients, are usually occurred in MG patients, and patient with the symptom of mastication fatigue was rarely reported. In addition, cardiological investigations have been performed in SBMA patients and several ECG alterations were identified. Here we report an SBMA patient presenting with a rare onset symptom of mastication fatigue, who has been detected with a positive titin antibody in the serum and showed a WPW pattern electrocardiogram. Case presentation The patient showed mildly progressive fatigue in the muscles of mastication over 3 years. Neurological examination showed facial muscle weakness and a wasting tongue with fasciculations, but the weakness, wasting, or fasciculations were not obvious in the limbs. 3-Hz RNS showed a decremental response in bilateral orbicularis oculi. The test of titin antibody was positive in the serum, and the electrocardiogram showed a WPW pattern ECG. Genetic analysis revealed an increased number (39 repeats) of tandem CAG repeats in the AR gene, which confirmed the diagnosis of SBMA. The fatigue symptom was significantly improved after oral pyridostigmine bromide treatment. Conclusion This case calls for more attention to muscular fatigue as the onset symptoms of Kennedy’s disease. ECG screening is of importance in SBMA patients and further studies are needed to investigate the titin antibody in SBMA patients as well as other neurogenic disorders.